NbTMP14 Is Involved in Tomato Spotted Wilt Virus Infection and Symptom Development by Interaction with the Viral NSm Protein - Jin Zhan; Huiping Shi; Weimin Li; Chao Zhang; Yongqiang Zhang (Viruses, 2021)
Tomato spotted wilt virus (TSWV) is one of the most destructive plant viruses, causing severe losses in many important crops worldwide. The non-structural protein NSm of TSWV is a viral movement protein that induces viral symptoms. However, the molecular mechanisms by which NSm contributes to symptom development are unclear. Here, we present evidence that NSm directly interacts with Nicotiana benthamiana chloroplast thylakoid membrane protein TMP14 (NbTMP14) by yeast two-hybrid and bimolecular fluorescence complementation (BiFC) assays. The interaction between NSm and NbTMP14 led to the translocation of the NbTMP14 protein from the chloroplast to the cytoplasm in TSWV-infected plants, and overexpressing NSm decreased NbTMP14 mRNA accumulation. In addition, abnormal chloroplasts and starch accumulation were observed in TSWV-infected plants. Silencing of NbTMP14 by TRV VIGS also showed similar results to those of TSWV-infected plants. Overexpressing NbTMP14 in transgenic N. benthamiana plants impeded TSWV infection, and silencing NbTMP14 in N. benthamiana plants increased disease symptom severity and virus accumulation. To our knowledge, this is the first report showing that the plant chloroplast TMP14 protein is involved in viral infection. Knowledge of the interaction between NSm and NbTMP14 advances our understanding of the molecular mechanisms underlying TSWV symptom development and infection.